2022
DOI: 10.1111/ene.15276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baseline infarct size on endovascular thrombectomy with or without intravenous alteplase in stroke patients: A subgroup analysis of a randomized trial (DIRECT‐MT)

Abstract: Background and purpose DIRECT‐MT showed that endovascular thrombectomy was noninferior to thrombectomy preceded by intravenous alteplase with regard to functional outcome in patients with acute ischemic stroke. In this post hoc analysis, we examined whether infarct size modified the effect of alteplase. Methods All patients with baseline Alberta Stroke Program Early Computed Tomography Score (ASPECTS) grades were included. The primary outcome was the 90‐day modified Rankin Scale (mRS) score. Multivariate ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…If replicated in a pooled analysis with more patients with more extensive perfusion deficits, our findings provide preliminary evidence that CTP parameters may not be able identify patients who are less likely to benefit from IVT prior to EVT. Similar to our findings, a recent post hoc analysis of the DIRECT-MT trial showed that the baseline infarct sizeestimated using ASPECTS -did not modify the treatment effect of IV alteplase prior to EVT [12]. This is in line with subgroup analyses from the Direct Endovascular Thrombectomy vs Combined IVT and Endovascular Thrombectomy for Patients With Acute Large Vessel Occlusion in the Anterior Circulation (DEVT) and The Direct Mechanical Thrombectomy in Acute LVO Stroke (SKIP) trials which did not show treatment effect heterogeneity based on ASPECTS dichotomized into ASPECTS <8 vs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…If replicated in a pooled analysis with more patients with more extensive perfusion deficits, our findings provide preliminary evidence that CTP parameters may not be able identify patients who are less likely to benefit from IVT prior to EVT. Similar to our findings, a recent post hoc analysis of the DIRECT-MT trial showed that the baseline infarct sizeestimated using ASPECTS -did not modify the treatment effect of IV alteplase prior to EVT [12]. This is in line with subgroup analyses from the Direct Endovascular Thrombectomy vs Combined IVT and Endovascular Thrombectomy for Patients With Acute Large Vessel Occlusion in the Anterior Circulation (DEVT) and The Direct Mechanical Thrombectomy in Acute LVO Stroke (SKIP) trials which did not show treatment effect heterogeneity based on ASPECTS dichotomized into ASPECTS <8 vs.…”
Section: Discussionsupporting
confidence: 91%
“…ASPECTS 8–10 [ 2 , 6 ]. Furthermore, in the DIRECT-MT trial, patients with extensive baseline infarction (i.e., ASPECTS 0–4) were highly unlikely to achieve functional independence at 90 days regardless of IVT administration prior to EVT [ 12 ]. More specifically, only 3/25 (12%) patients with ASPECTS 0–4 achieved functional independence in the EVT alone arm compared to 5/31 (16%) of patients with ASPECTS 0–4 in the IVT prior to EVT arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Jia et al report a sub‐analysis of the Direct Intraarterial Thrombectomy to Revascularize Acute Ischemic Stroke Patients with Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals (DIRECT‐MT) trial [8]. The authors examine whether the extent of ischaemic injury on the pre‐treatment computed tomography (CT) brain (assessed using the Alberta Stroke Program Early CT Score, ASPECTS) modified the effect of the direct versus bridging treatment strategy.…”
mentioning
confidence: 99%